Balancing Earth science careers in an unequal world - Nadia Testani; Lucía M. Cappelletti; Leandro B. Díaz; Camila Prudente; Valentina Rabanal; Julia Mindlin; Reyk Börner; Divya David T; Ismaila Diallo; Inés M. Leyba; Marisol Osman; Andrés Tangarife-Escobar (Communications Earth & Environment)
Unequal research experiences among Earth scientists from around the world are an obstacle to achieving sustainability. We assess challenges and propose ways to balance the careers of early- and mid-career researchers in the Global South with those in the Global North.